1972
DOI: 10.1530/jrf.0.0300335
|View full text |Cite
|
Sign up to set email alerts
|

Dna Content and Morphological Properties of Presumably Aneuploid Spermatozoa of Tobacco Mouse Hybrids

Abstract: A sharp reduction in fertility of the F1 hybrids between the tobacco mouse (M. poschiavinus) and the laboratory mouse can be attributed to irregular segregation of trivalents in meiotic anaphase I. In male meiosis, more than 50% of aneuploid secondary spermatocytes are produced. The cytophotometric measurements of the relative Feulgen-DNA content of cytologically mature, morphologically normal spermatozoa revealed a significantly greater variation in F1 males as compared to M. poschiavinus and the laboratory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…They also show that there were no hypermodal cells recorded in either the normal rams or in the homozygous rams (t1t1 and t3t3) and the number of cells with 29 chromosome arms is higher for the hétérozygotes than for the homozygotes and normal rams. This is similar to the results described from similar studies on the tobacco mouse (Döring et al, 1972;Cattanach & Moseley, 1973).…”
Section: Cytogenetic Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…They also show that there were no hypermodal cells recorded in either the normal rams or in the homozygous rams (t1t1 and t3t3) and the number of cells with 29 chromosome arms is higher for the hétérozygotes than for the homozygotes and normal rams. This is similar to the results described from similar studies on the tobacco mouse (Döring et al, 1972;Cattanach & Moseley, 1973).…”
Section: Cytogenetic Methodssupporting
confidence: 91%
“…The analysis of large numbers of M II cells in the mouse has been facilita¬ ted by the use of colchicine in the living animal (Tettenborn & Gropp, 1970;Döring et al, 1972;Cattanach & Moseley, 1973) …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been shown that spermatozoa from subfertile males are more susceptible to heat denaturation (Evenson et al, 1980 Staining nuclei with 7-AMD induced an increase in the size of the nuclei that may have been due to the prolonged exposure to either the dye or the buffer overnight (see Balhorn et al, 1985). However, the preferential increase in length may be related to the observation that chromatin, inside sperm nuclei, is in a cholesteric configuration (Sipski & Wagner, 1977 (Döring et al, 1972) failed to discriminate abnormal sperm heads from normal ones. However, a UV absorption analysis of F, hybrids between Mus musculus and Mus poschiavinus showed a higher mean DNA content but the differences were not statistically significant (Stolla & Gropp, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that neardiploid spermatozoa are due to a failure of the second meiotic division. INTRODUCTION Chromosomal disorders in human (Carr, 1965(Carr, , 1970Boue & Boue, 1973) and other mammalian (McFeely, 1967;Ford, 1970) (Gropp, Tettenborn & von Lehmann, 1970; (Döring, Gropp & Tettenborn, 1972), and (2) on the finding that F1 hybrid males mated with female laboratory mice generate about 50% or more aneuploid (monosomic or trisomie) zygotes (Gropp, 1973 Döring et al, 1972).…”
mentioning
confidence: 99%
“…In fifty morphologically normal spermatozoa of each of the six males per group, the total extinction ( ) at 260 nm (maximum for DNA), 280 nm (maximum for proteins) and 313 nm (correction for non¬ specific light loss) was recorded using the Universal Microspectrophotometer ZEISS (UMSP I). On the basis of these measurements, the DNA content per sperm head (M) was calculated according to the formula M = 0-92 ZE260nm -0-75 280 -0-25ZE313nm (see Stolla, 1968 (Döring et al, 1972). There is, however, a marked shift to a higher mean value of the DNA content per spermatozoon in F, hybrid males compared with that found in the parental strains, though it is significant only by comparison with the laboratory mouse.…”
mentioning
confidence: 99%